The Modulation of Spatial Working Memory by Emotional Stickers and Facial Expressions - Li, Yueying; Li, Shengnan; Ren, Yanna; Chen, Jianxin; Yang, Weiping (Frontiers in Psychology, 2020)
This article aims to investigate the interaction effects of emotional valence (negative, positive) and stimulus type (sticker, face) on attention allocation and information retrieval in spatial working memory (WM). The difference in recognition of emotional faces and stickers was also further explored. Using a high-resolution event-related potential (ERP) technique, a time-locked delayed matching-to-sample task (DMST) was employed that allowed separate ERP investigations of target, delay, and probe phases. The results indicated that negative emotion can interfere with spatial WM at the behavioral level and catch early attention in information encoding, which was indicated by the augmentation of the attention-related P200 amplitude. In the delay phase, the N170 component represents facial specificity and showed a negative bias against stickers. For information rehearsal, the increase in the emotion-related late positive component (LPC) showed that positive emotion could damage spatial WM and consume more cognitive resources. Moreover, stickers have the ability to catch an individual’s attention throughout the whole course of spatial WM with larger amplitudes of the attention-related P200, the negative slow wave (NSW), and the LPC. These findings highlight the role of stickers in the different phases of spatial WM, and confirmed that the sticker contains potential emotional mechanisms.